Penerapan Kolaborasi Pemberian Inhalasi dengan Close Suction untuk Bersihan Jalan Napas Tidak Efektif pada Pasien Ny. R Terpasang Endotracheal Tube di Ruang ICU RSUD Sidoarjo - Fariqoini, Ayyul; Sholehah, Baitus; Fauzi, Ahmad Kholid (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Ineffective airway clearance is a condition where the patient is unable to cough effectively, often caused by thick or excessive secretions due to infection. The objective of this intervention is to address ineffective airway clearance in patients with an endotracheal tube in the ICU of RSUD Sidoarjo. After inhalation and close suction procedures, observations showed improvements in vital signs and respiratory rate, along with significant reduction of secretions. This led to an increase in peripheral oxygen saturation (SpO2), improving oxygen supply to the body. Based on the case study, the nursing intervention for ineffective airway clearance conducted over 2 x 8 hours showed partial success in resolving the issue. Following a thorough nursing assessment, the diagnosis for patient Mrs. R was determined as ineffective airway clearance related to airway spasms, evidenced by inability to cough, excessive sputum, and ronchi sounds.